Identification of LecRLK gene family in Cerasus humilis through genomic-transcriptomic data mining and expression analyses. - Hongyan Han; Xiaopeng Mu; Pengfei Wang; Zewen Wang; Hongbo Fu; Yu Gary Gao; Junjie Du (PLoS ONE)
Lectin receptor-like protein kinases (LecRLKs) have been shown to be involved in plants' responses to various biotic and abiotic stresse factors. Cerasus humilis is an important fruit species widely planted for soil and water conservation in northern China due to its strong tolerance to drought and salinity stresses. In this study, a total of 170 LecRLK family genes (125 G-types, 43 L-types and 2 C-types) were identified in the newly released whole-genome sequences of C. humilis. Furthermore, nine representative LecRLK genes in young plants of C. humilis under varying drought and salinity stresses were selected for qRT-PCR analysis. Our systematic comparative analyses revealed the active participation of these nine LecRLK genes in the salt and drought stress responses of C. humilis. The results from our study have provided a solid foundation for future functional verification of these LecRLK family genes and will likely help facilitate the more rapid and effective development of new stress resistant Cerasus humilis cultivars.